Legal Analysis of the Validity of E-Stamps in the Creation of Notarial Deeds and PPAT Deeds Based on the Stamp Duty Law and the Notary Position Law - Putri, Jesika Ananda; Farina, Thea; Wijaya, Andika (Journal of Law, Politic and Humanities, 2025)
The development of digital technology has driven transformation in various fields, including the administration system and legal proof through documents. One significant innovation is the implementation of electronic stamps (e-stamps) as an alternative to physical stamps based on Law No. 10 of 2020 on Stamp Duty. E-stamps offer efficiency, ease of access, and the potential to prevent document forgery. However, its application in authentic deeds made by Notaries and Land Deed Officials (PPAT) raises legal questions, particularly concerning its validity and legal certainty. Article 1868 of the Civil Code (KUH Perdata) stipulates that authentic deeds must be made by or before a public official in accordance with the form specified by law. Meanwhile, the Notary Position Law has not explicitly accommodated the use of e-stamps. This research uses a normative approach with doctrinal and legislative methods to analyze the compatibility of e-stamp usage in authentic deeds. The study's findings show that although substantively e-stamps are valid as a tool for collecting duties, there is a legal gap in the technical regulations concerning their use in notarial and PPAT deeds. This gap creates legal uncertainty that may affect the evidentiary power of authentic deeds in court. Therefore, there is a need for more harmonious regulations and clear technical guidelines so that the digital transformation in notarial practices can be effectively implemented without reducing legal certainty.